Obtaining Mutant Strain of Chlamydomonas reinhardtii and Studying Its Phenotypic Characteristics. (Experimental biology, 2015)
UV mutagenesis is a powerful tool for obtaining mutant strains of microalgae for using in biotesting of the pollutedaquatic ecosystems. UV irradiation has a strong mutagenic agent, compared with chemical mutagenesis, UVmutagenesis offers many advantages such as less pollution, simple operation, and sterile cultivation condition. In this study the phenotypic characteristics of the wild and mutant strains of the green microalgae Chlamydomonas reinhardtii (CC 1021) were investigated. From the obtained results, selection of the mutant colony after irradiation time 1min. and named CC1021Mut1 strain. The mutant strain showed differences in phenotypic features such as color and size of colonies in the solid medium and also different color in the liquid medium. The mutant cells under microscope appeared different in size and color than the wildtype cells.
Keywords: UV mutagenesis; mutant strain Chlamydomonas reinhardtii CC 1021 Mut1; Phenotype (light green color and small size colonies)